Two Clinical Cases of Secondary Neoplasia After Remission of Hodgkin’s Disease - Vanya Slavcheva (Journal of Biomedical & Clinical Research)
Hodgkin’s disease is one of the most common lymphomas in young people. In such cases, long-lasting hematological remissions are achievable using therapeutic regimens, including combined radiotherapy and chemotherapy. This publication aims to present clinical cases from our practice in patients with Hodgkin’s disease in whom the occurrence of second neoplasia is probably causally related to the treatment of Hodgkin’s lymphoma. We present two clinical cases of women with established secondary neoplasia (breast carcinoma, diffuse large B cell lymphoma) 20 years after treatment for Hodgkin’s disease had been completed. The probability of developing another neoplastic disease, leading to increased mortality in these patients, requires updating the recommendations for secondary prevention in oncology.